The implementation of No-fault Based Liability (NFBL) system for medical negligence in Malaysia / Mohd. Izham Mohd. Marzuki, Nurul Adeela Syafiqa Annuar and Nurul Hafizah Mohammad Pauzi - Mohd. Marzuki, Mohd. Izham; Annuar, Nurul Adeela Syafiqa; Mohammad Pauzi, Nurul Hafizah (2012)
NFBL had been receiving the spotlight in the last few decades. Many countries had considered of changing their insurance system into a NFBL system. In this research, researcher had given a special focus on NFBL in medical negligence. Medical accidents are on the rise in Malaysia, the current FBL system in order to optimize the usage of public money from wasting it. There is also the case of time taken to settle a case, it would take a long time to complete a case and acquire the compensation from the defendant. The researchers had taken an approach of going through previous studies of local scholars and also compare with some scholars of other countries. Interviews with the Malaysian Medical Council, National Consumer Complaints Centre and the prominent scholar in NFBL, Prof. Dr. Puteri Nemie Jahn Kassim also had taken place to have an inside view of the current system. Results from the study had concluded from the many types of NFBL, Malaysia had seen to be suited with the choice system after many comparisons and insights from the interviews that were done during the research. Malaysia also had seen to be not suited for a Pure NFBL system which costs much more and will be a burden to the country.